The Township and the Gangster in Tsotsi : Local and Global Aspirations of the New South African Cinema - (:unkn) unknown (My University, 2012)
After the downfall of apartheid, the advent of democracy in 1994 led South Africa to a restructuring of its institutions that reached beyond the strictly political realm, also reshaping policy in terms of arts and culture. Decisions were made to reorganise the film industry and assign it new objectives in the context of postapartheid nation-building. Over a decade later, the South African film production has acquired a place on the international scene that can be attested by the worldwide success of Neill Blomkamp's District 9 1 or again the 2005 Academy Award for Best Foreign Language Film received by Gavin Hood's Tsotsi. 2 However, as far as box-office is concerned, the South African audience still favours American feature films over their local counterparts. 3 To counteract this, the South African film industry has been attempting to concomitantly touch national and international audiences. Local objectives include making commercially viable films that succeed at the national box-office while focusing on telling authentic local stories about South African realities. Meanwhile, global ambitions mean making internationally competitive films that will project an image of South Africa abroad. In more practical terms, the industry aspires to a commercial and critical success abroad, and to fruitful co-productions. The aim of this article is to analyse the tensions that arise from these conflicting goals. In that perspective, this paper proposes to examine how local and global aspirations came into play in the making of one individual South African feature film, Gavin Hood's Tsotsi (2005). Tsotsi was shot in 2004 and released in 2005 in South Africa and in the course of 2006 internationally. The story of a gangster's redemption was shot on a five million dollar budget, in Kliptown, in the famous township of Soweto, near Johannesburg. Analysing Tsotsi seems particularly relevant due to the film's commercial success locally and abroad, to its international
Keywords: African Research